PENINGKATAN PENGETAHUAN DETEKSI DINI KANKER PAYUDARA PADA WANITA PEKERJA PABRIK KARET DI KOTA PALEMBANG - Krisna Murti; Pariyana Pariyana; Iche Andriyani Liberty; Mariana Mariana; Putri Mahirah Afladhanti; Dwi Tantri Marylin (As-Sidanah, 2023)
Breast cancer is a global and national health concern that affects women worldwide and it is responsible for causing the highest number of cancer-related deaths annually. Additionally, the high incidence of breast cancer imposes a financial burden on the nation. Early breast cancer detection in reproductive age women using breast self-examination (SADARI) was chosen due to simple, inexpensive, and non-invasive procedure. SADARI is very necessary to find out any breast abnormalities so that they can be treated early. This community service project involved providing counseling to female workers in a rubber factory at Palembang city. The counseling was delivered through a lecture and demonstration of SADARI using mannequin. A pre-and post-test questionnaire containing 30 questions was utilized as the evaluation instrument. This activity aimed to measure the increase in knowledge about breast cancer early detection with SADARI among female workers in a Palembang city rubber factory. After counseling, the mean score was 1.42 points higher than before counseling, with p-value of 0.155. The results showed non-significant increase in knowledge before and after the counseling session.